Optical fibre measuring instrument / Azizi Mamat - Mamat, Azizi (1997)
The main objective of this project is to improve the design of a low cost solidstate Optical Fibre measuring instrument. This instrument employs opto-electronic devices such as light emitting diodes (LEDs) as a light source and semiconductor photodiode (PD) as a photodetector. A fibre optie cable is used as a media or transmission link to link between light source sensor and photodetector. The improvement involved the construction of Power Supply and circuitry modification. The instrument will be interfaced to a personal computer (PC). The output signal from the measuring instrument will be interfaced through a parallel analogue to digital card before entering the PC. The PC will process and display this signal. A Turbo C++ programming is used to manipulate the input data continuously and transform the signal to an on-line instrument.